In Silico Study of Bioactive Compounds from Koro Benguk (Mucuna pruriens (L.) DC.) as Potential Modulators of CYP7A1 for Hypercholesterolemia Therapy - Cleofany Aurhelya Paradhise; Trisna Kumala Sari (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Hypercholesterolemia is a major risk factor for cardiovascular diseases and remains a significant global health concern. Cholesterol 7α-hydroxylase (CYP7A1), the rate-limiting enzyme in the classical bile acid synthesis pathway, plays a crucial role in hepatic cholesterol catabolism and represents a promising therapeutic target for cholesterol regulation. Natural product-derived compounds have attracted increasing attention as potential antihypercholesterolemic agents due to their structural diversity and biological activities. However, studies evaluating phytochemicals from Mucuna pruriens as CYP7A1 modulators remain limited, particularly those integrating molecular docking with pharmacokinetic prediction. Therefore, this study aimed to evaluate the potential of bioactive compounds from Mucuna pruriens as modulators of CYP7A1 using an in silico approach. Twenty-eight phytochemical compounds identified through GC-MS profiling were screened using Lipinski’s Rule of Five. Selected compounds were further analyzed by molecular docking against the CYP7A1 protein (PDB ID: 3DAX), followed by ADMET prediction. Docking protocol validation through redocking of the native ligand showed good conformational agreement at the active site (RMSD < 2 Å), confirming the reliability of the docking parameters. Binding affinity and RMSD were used to evaluate ligand–protein interaction stability. Sterculic acid exhibited the strongest binding affinity with a docking score of −6.6.1 kcal/mol and RMSD of 1.51 Å, slightly stronger than the reference ligand 7-ketocholesterol (−7.335 kcal/mol). Interaction analysis revealed hydrogen bonding with key residues, including Asn126 and Lys98, as well as hydrophobic interactions within the active pocket. Other fatty acid derivatives, including octadecanoic acid and heptadecanoic acid, also showed competitive binding energies. ADMET prediction indicated high intestinal absorption (HIA > 90%), no CYP3A4 inhibition, and low predicted toxicity. These results highlight sterculic acid as a promising CYP7A1 modulator and support the potential of Mucuna pruriens phytochemicals for further molecular dynamics studies and experimental validation in the development of hypercholesterolemia therapy.